Personal and Environmental Influences on Smoke-Free AreaCompliance : a Literature review - Eka Rachmawati; Annisa Nurrachmawati; Nur Rohmah (Faculty of Public Health Mulawarman University, Indonesia, 2025)
The government has established smoke-free policies, but despite the issuance of various regulations, the implementation of smoke-free areas in the field still faces serious challenges, one of which is low public compliance. Factors that influence compliance include personal factors and environmental factors. Objective : The purpose of this study is to conduct a literature review of studies that investigate the influence of personal factors and environmental factors on compliance with no-smoking areas in public facilities. Research Methods/ Implementation Methods : The research method used in this study is a Systematic Literature Review (SLR) using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Search from Google Scholar, PubMed, and Research Gate, using the keywords